If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4y = 3x + 6 Reorder the terms: 2x + 4y = 6 + 3x Solving 2x + 4y = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2x + -3x + 4y = 6 + 3x + -3x Combine like terms: 2x + -3x = -1x -1x + 4y = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 -1x + 4y = 6 + 0 -1x + 4y = 6 Add '-4y' to each side of the equation. -1x + 4y + -4y = 6 + -4y Combine like terms: 4y + -4y = 0 -1x + 0 = 6 + -4y -1x = 6 + -4y Divide each side by '-1'. x = -6 + 4y Simplifying x = -6 + 4y
| 8-(-14)+4= | | 5x-3x+13=x+8 | | 2x-95+9x=37 | | n+(-3)=-0.6 | | 5(c+8)c=5 | | 6y^2-12y^3= | | (2x-y)x^2+(2x+1)(2x-y)= | | 2(3x-7)+4(3x+2)=6 | | 50=18+4t | | 7-(2b)=12 | | 7-2b=12 | | x^4-8x^2+36=0 | | -(x+3)=5x-9 | | 2(a-6)=-9 | | 4x^2+10x+256=0 | | 8-6(6+8p)=-8p+12 | | 4b+56=64 | | 35r^2+ry-5xr-2xy= | | x+11x-151=101 | | 3m^3+24p^3=0 | | 6x-5=5x+10 | | 12r+(-12)= | | 6+2x-3=4x+2 | | 10m-23=27 | | r(9r+1)=8 | | 3+6x-3x=7+3x-6x | | 3+6x-3x=7+6x-3x | | -x+1=x-1 | | y=-2b+7mx | | -48+11x-8x=36 | | K^2-6=5k | | 5x+12x-123=132 |